Комбінований метод лікування гіпокортицизму - Турчин, І. С.; Ларін, О. С.; Січінава, Р. М.; Сидоренко, Л. М.; Дроздович, І. І.; Коваленко, М. О.; Доготар, В. Б.; Коноваленко, І. В.; Смоляр, В. А. (Clinical Endocrinology and Endocrine Surgery, 2009)
Xenotransplantation of adrenal gland organ cell culture with hepatocytes in postadrenalectomic syndrome is not a competing method of treatment but is a ancillary to the traditional gluco mineralocorticoid therapy. Xenotransplantation of adrenal gland organ cell culture with hepatocytes efficiency in hypocorticism is about 8-12 months. Doses of synthetic hormonal medications decrease after the xenotransplantation of adrenal gland organ cell culture with hepatocytes in 25-75% and in some cases synthetic hormonal medications are periodicaly canceled.